2010
DOI: 10.1159/000319209
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration between Allergists and Pharmacists Increases β-Lactam Antibiotic Prescriptions in Patients with a History of Penicillin Allergy

Abstract: Background: Over 90% of patients with a history of penicillin allergy have negative penicillin skin tests. Pharmacists are trained to identify and resolve medication-related problems. We hypothesized that collaboration between allergists and pharmacists to identify and evaluate patients with a history of penicillin allergy would increase β-lactam antibiotic prescription. Methods: We conducted a prospective observational study in which patients with a history of penicillin allergy were identified and educated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…71, 144, 145 Small pilot studies have demonstrated pharmacy led referral systems, antibiotic allergy stewardship rounds, and direct oral provocation programs can safely increase simple beta-lactam use and reduce restricted antibiotic usage and hospital costs. 14, 63, 126, 135, 146152 Recent published experiences with inpatient allergy testing, either pharmacist, allergist or infectious diseases led, have also demonstrated improved uptake of preferred beta-lactam therapies. 134, 153155 Targeted antimicrobial stewardship programs have demonstrated a reduction in restricted antibiotic usage, with such an intervention.…”
Section: Collaboration– New Pathways and Partnershipsmentioning
confidence: 99%
“…71, 144, 145 Small pilot studies have demonstrated pharmacy led referral systems, antibiotic allergy stewardship rounds, and direct oral provocation programs can safely increase simple beta-lactam use and reduce restricted antibiotic usage and hospital costs. 14, 63, 126, 135, 146152 Recent published experiences with inpatient allergy testing, either pharmacist, allergist or infectious diseases led, have also demonstrated improved uptake of preferred beta-lactam therapies. 134, 153155 Targeted antimicrobial stewardship programs have demonstrated a reduction in restricted antibiotic usage, with such an intervention.…”
Section: Collaboration– New Pathways and Partnershipsmentioning
confidence: 99%
“…Recent studies have highlighted increased use of restricted antibiotics and inappropriate prescriptions in those with antibiotic allergy labels [2]. The engagement of hospital pharmacists is essential; programs using direct allergy referrals from pharmacy departments have aided delabeling initiatives [12, 20]. A multidisciplinary model involving allergists, immunologists, ID physicians, and pharmacists is most likely to engage clinicians and deliver an effective service [21].…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [89] demonstrated that pharmacist-facilitated referral to allergists can increase β-lactam antibiotic prescriptions in patients with a reported penicillin allergy, as 94% of patients referred to an allergist were SPT/IDT-negative. Furthermore, 66% of those referred to an allergist were subsequently prescribed a β-lactam compared with 26% who were not referred ( P <0.0001).…”
Section: An Antibiotic Allergy and Antimicrobial Stewardship Partnersmentioning
confidence: 99%